(untitled) (Tabanque. Revista Pedagógica, 2020)
In this contribution the author attempts to analyze, without any pretense of completeness, a model of teacher training oriented to the sharing of knowledge in action and professional experiences, through the acquisition of new skills in the field of methods and techniques of active teaching, cooperative and laboratorial, able to create spaces for dialogue and self-reflection among peers. To this end, it was decided to analyze the focus group not only as a research device, but also as a didactic-training methodology within a path of professional learning among teachers, supporting the dissemination of training and learning development groups between equal within the convivial community of practices